Analysis Of Budget Realization Report (Lra) At Hasanuddin Damrah Manna Regional Public Hospital, South Bengkulu Regency - Eva Listeriany; Neri Susanti; Ramadan Subhi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
The analysis of the budget realization report at Hasanuddin Damrah General Hospital in Manna, South Bengkulu Regency will help the hospital identify areas of the budget that need improvement or further attention to ensure more targeted budget utilization. The objectives of this research are: 1) To understand the comparison between the planned budget and the realized budget at Hasanuddin Damrah General Hospital in Manna, South Bengkulu Regency over a certain period; 2) To identify the factors influencing discrepancies between the planned budget and the realized budget at Hasanuddin Damrah General Hospital; 3) To determine the effectiveness and efficiency of budget utilization at Hasanuddin Damrah General Hospital. The analysis method used in this study is a qualitative descriptive method employing the interactive model of Miles and Huberman. The research results indicate that there is a variance between the planned budget and the realized budget; however, overall, the budget realization at the hospital is classified as quite good. The analysis shows that the budget realization tends to approach or even exceed the target, despite differences between the plan and realization. The discrepancies between the budget and realization are influenced by various internal and external factors. Internal factors include fluctuations in patient visits, disease trends, and the efficiency of service unit performance. Meanwhile, external factors such as changes in government regulations, procurement policies, and the dynamics of volume-based service revenue also affect the accuracy of budget planning. The budget utilization is considered effective, yet challenges remain in maintaining expenditure efficiency. The effectiveness of budget utilization in 2023 reached over 100%, indicating the hospital's ability to optimize revenue and respond to service needs. However, spending efficiency has not been fully optimal, especially in 2024, indicating signs of overspending due to a lack of control over actual needs.